Islamic Legal Analysis of the Concept of Maintenance in the Context of a Working Wife - Muhamad Hikmal Alfajri; Tamy Rahma Sya'ara; Reno Anugrah Pratama (Moccasin Journal De Public Perspective, 2026)
This study examines the legal construction of maintenance obligations within Islamic family law in the contemporary context of working wives. It adopts a doctrinal and normative-comparative approach, integrating classical jurisprudence, Indonesian positive law, judicial practices, and contextual socioeconomic data within a maqāṣid al-sharī‘ah framework. The findings confirm that maintenance remains a fundamental and non-transferable obligation of the husband across doctrinal, statutory, and judicial dimensions, unaffected by the wife’s income. However, judicial practice demonstrates contextual flexibility in determining the proportionality of financial support through case-based reasoning. The analysis further shows that this legal construction aligns with broader objectives of economic protection, fairness, and family stability. This study contributes by offering an integrative normative framework that is contextualized by contemporary social realities, demonstrating the capacity of Islamic family law to adapt without compromising its core principles.